2022
DOI: 10.3390/cancers14184418
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Aldehyde Dehydrogenase, PD-L1 and Tumor-Infiltrating Lymphocytes with Pathologic Response and Survival in Breast Cancer

Abstract: Aldehyde dehydrogenase 1A1 (ALDH1A1) is a cancer stem cell (CSC) marker related to clinical outcomes in breast cancer (BC). The aim of this study was to analyze the relationship between ALDH1A1, programmed death ligand 1 (PD-L1) and tumor-infiltrating lymphocytes (TILs) in triple negative (TN) and human epidermal growth factor receptor 2-positive (HER2+) BC tumors, and its association with clinicopathological characteristics and outcomes. A retrospective, historical cohort study of patients diagnosed with earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Notably, Liu et al previously proposed that high ALDH1A1 expression in tumor tissues could independently predict favorable outcomes in TNBC 39 . Flores et al also reported a correlation between ALDH1A1 expression and pCR 40 . Althobiti et al specifically evaluated ALDH1A1 immunoexpression and found a significant association with poor survival, particularly in the luminal B and TNBC subtypes 41 .…”
Section: Discussionmentioning
confidence: 85%
“…Notably, Liu et al previously proposed that high ALDH1A1 expression in tumor tissues could independently predict favorable outcomes in TNBC 39 . Flores et al also reported a correlation between ALDH1A1 expression and pCR 40 . Althobiti et al specifically evaluated ALDH1A1 immunoexpression and found a significant association with poor survival, particularly in the luminal B and TNBC subtypes 41 .…”
Section: Discussionmentioning
confidence: 85%